The City by the Pool Assessing the Archaeology of the City of Lincoln - Vince, Alan G. (Historic England, 2003)
This volume offers a new and up-to-date synthesis of Lincoln's long history as a major city and regional capital, from prehistory to 1945. The 'City by the Pool' was a major religious centre long before the Roman invasion and from bronze-age shamans to early Baptists people have always been attracted here for spiritual as well as mundane purposes. The authors argue for the presence of a major ritual causeway of the late Bronze and Iron Age and outline the extent to which ritual monuments also contributed to the character of Roman Lincoln. This book is based on more than a hundred publicly-funded excavations and building surveys undertaken between 1945 and 2000. It surveys all aspects of city life, from housing and fortifications to the water supply and rubbish disposal. It includes a CD Rom with a Geographic Information System (GIS) and a relational data-base known as LARA (the Lincoln Archaeological Research Assessment).